Interpersonal Relations in Ethics of Science and Technologies - Peter Kondrla; Eva Durkova (Communications - Scientific letters of the University of Zilina, 2018)
Science and technologies are defined in their foundations as tools for understanding the world. They are tools for simplifying and facilitating the life of man and society. Science and technologies are oriented towards production. The absence of humanistic aspect is leading to science not reflecting human as a person but as an object. The result of this is depersonalization. Thanks to this, manipulation is present in interpersonal relationships. Another thing that adds to this fact are new technologies which make manipulation and control easier. Concrete ethical solution to the problem of depersonalization are personalist ethics which represent the return to the human being and the respect of its dignity. Ethics of science and technologies must come from respect towards the dignity of a person. This has to reflect in the education of users of modern communication technologies. Then the ethics of science and technologies will have an actual impact on the quality of interpersonal relationships.